Statistical Meso-Mechanics of Damage and Failure: How Microdamage Induces Disaster Series Publication of Multiscale Mechanics - Bai, Yilong; Xia, Mengfen; Ke, Fujiu (Springer Nature Singapore : Imprint: Springer, 2019)
This book introduces a trans-scale framework necessary for the physical understanding of breakdown behaviors and presents some new paradigm to clarify the mechanisms underlying the trans-scale processes. The publication of this book based on the interaction of mechanics and statistical physics can help to deepen the understanding of how microdamage induces disaster and benefit the forecasting of the occurrence of catastrophic rupture. The readers of the book would be graduate students, researchers, engineers working on civil, mechanical and geo-engineering, etc. However, people with various background but interested in disaster reduction and forecasting, like applied physics, geophysics, seismology, etc., may also be interested in the book. .